SATISFACTION OF EXCELLENT SERVICE TRAINING PARTICIPANTS WITH THE KIRKPATRICK MODEL AT ALIA HOSPITAL DEPOK - Dewi, Nur Fadilah (UI Scholars Hub, 2024)
The study aims to improve the quality of human resources and services at Alia Hospital Depok through evaluation of training programs. The approach used is the Donald Kirkpatrick model evaluation which is a common method used in evaluating the effectiveness of training. The main problem faced by Alia Hospital Depok is the lack of evaluation conducted on the training programs that have been held. Therefore, training evaluation needs to be considered to improve the quality of human resources and services provided. The research method used is a survey by distributing questionnaires to service excellent training participants to evaluate their reactions to the training program. The findings show that the majority of training participants were satisfied with the training program and gave positive feedback to the training organizers. With a good and measurable evaluation, the management of Alia Hospital Depok can get feedback on the success of the training and improve the quality of human resources and services provided in the hospital. Therefore, evaluation of training programs needs to be an important part of efforts to improve the quality of human resources and health services at Alia Hospital Depok. can be done effectively.